[6]-Shogaol/β-CDs inclusion complex: preparation, characterisation, in vivo pharmacokinetics, and in situ intestinal perfusion study. (4th July 2019) - Li, Ran; Bao, Rui; Yang, Qiu-Xuan; Wang, Qi-Long; Adu-Frimpong, Michael; Wei, Qiu-Yu; Elmurat, Toreniyazov; Ji, Hao; Yu, Jiang-Nan; Xu, Xi-Ming
Abstract: Aims: The aim was to improve the absorption and bioavailability of [6]-shogaol with β-cyclodextrin (β-CD) prior to in vitro and in vivo evaluation. Methods: [6]-Shogaol/β-CDs inclusion complexes (6-S-β-CDs) were developed using saturated aqueous solution method and characterised with appropriate techniques. The absorption and bioavailability potential of [6]-shogaol was evaluated via in vivo pharmacokinetics and in situ intestinal perfusion. Results: The results of characterisation showed that 6-S-β-CDs (drug loading, 7.15%) were successfully formulated. In vitro release study indicated significantly improved [6]-shogaol release. Pharmacokinetic parameters such as C max, AUC0–36 h, and oral relative bioavailability (about 685.36%) were substantially enhanced. The in situ intestinal perfusion study revealed that [6]-shogaol was markedly absorbed via passive diffusion in the intestinal segments, and duodenum followed by ileum and jejunum. Conclusions: Cyclodextrin inclusion technology could enhance the intestinal absorption and oral bioavailability of hydrophobic drugs like [6]-shogaol.